Stuck between medals and participation: an institutional theory perspective on why sport federations struggle to reach Sport-for-All goals - Thomas De Bock; Jeroen Scheerder; Marc Theeboom; Bram Constandt; Mathieu Marlier; Tom De Clerck; Annick Willem (BMC, 2022)
Abstract Background Sport-for-All emphasizes that every individual has the right to participate in sport. Despite all efforts to deliver Sport-for-All during the past decades, studies indicate that sport participation rates have been stagnating, whereas social inequalities in sport continue to exist. By applying an institutional theory lens, this study sheds light on how the dual mission of sport federations, i.e., providing Sport-for-All and high performance sport, affects the Sport-for-All projects of Flemish sport federations (e.g., amount of projects and target groups). In particular, Sport-for-All projects have to reduce barriers to engage in the sport system and be supported by a sport federation. Furthermore, this study seeks to better understand the impact of the underlying institutional logic on the institutional pressure and legitimacy of the sport federations. Method This study implemented a cross-sectional field study in sport federations. In particular, the sport federations selected for our study are the 47 Flemish sport federations. Both qualitative (i.e., document analysis) and quantitative research methods (i.e., a new questionnaire was developed based on institutional theory) were applied in the study. Results Results indicated that sport federations are important partners in support of Sport-for-All projects, but also suggested that there is a discrepancy between the projects of the high performance-oriented and the Sport-for-All-oriented federations. Specifically, the high performance-oriented federations were targeting youth participants, whereas Sport-for-all-oriented federations aimed to reach disadvantaged groups. Furthermore, the results indicated that high performance-oriented federations endured more institutional pressure than Sport-for-All-oriented federations. Conclusion The results of our study indicated that the Sport-for-All projects of performance-oriented federations are often more superficial compared to Sport-for-All oriented federations, and that the latter federations play an important role in attaining public health targets. Moreover, policymakers should consider how they can optimize the role of the performance-oriented federations in the Sport-for-All delivery (e.g., they could function as a bridge to guide participants who prefer a less competitive setting towards Sport-for-All oriented federations).